Technology-Driven Disruption of Healthcare and 'UI Layer' Privacy-by-Design - Corrales Compagnucci, Marcelo; Fenwick, Mark; Haapio, Helena; Minssen, Timo; Vermeulen, Erik P. M. (Cambridge University Press, 2022)
The use of digital technologies in healthcare is changing how medical treatments are developed by researchers, delivered by medical professionals and experienced by patients. This chapter argues that a defining feature of this disruption is the emergence of medical apps that leverage algorithm-based AI systems. As the use of such apps and AI wearables goes mainstream and new players – notably ‘Super Platforms’ with digital rather than medical expertise – enter the healthcare sector, traditional medical services will be transformed. These developments pose several challenges for regulators and policymakers, most obviously in terms of privacy and data protection. Here, we examine how the emerging field of Legal Design can provide a more transparent infrastructure that embeds relevant legal protections in the user interfaces of healthcare products and services. A Privacy-by-Design approach focused on the user interface (UI) offers several advantages, most obviously greater transparency, accountability and human choice. The chapter offers real-world examples of design patterns that illustrate the value of UI-focused Privacy-by-Design in protecting sensitive information, enabling people to retain control of their personal data. The chapter concludes with some examples and reflects on the challenges in implementing Legal Design in an eHealth context.
Keywords: AI; algorithms; apps; design patterns; GDPR; healthcare; legal design; super platforms; UI layer privacy-by-design; data protection; privacy; fi=Talousoikeus|en=Business Law|